Successful Adjunctive Vincristine–Ivermectin Therapy for Pars Bulbus Glandis CTVT in Two Intact Male Dogs - Raju, Kangonu Anthony; Raju, Francis Sebastin; Kiran, Allada Uday; Likitha, Nuka; Paidi, Saranya (The Indian Journal of Animal Reproduction, 2026)
Two non-descript male dogs, aged two and four years, were presented with a history of bloody discharge, paraphimosis and pedunculated masses at pars bulbus glandis of penile shaft. Based on physical and cytological examinations, the con dition was diagnosed as Canine Transmissible Venereal Tumour (CTVT). The successful tumour remission was achieved using a weekly adjuvant chemotherapy protocol involving intravenous vincristine sulfate (0.5- 0.7 mg/m2 of body surface area) and subcutaneous ivermectin (0.2mg/kg b wt).